Coping Strategies and Psychological Interventions Among Traumatized African Migrants in the Western World: a Comparison Between Rwandans in Finland and Belgium - Banyanga, Jean d’Amour; Österman, Karin; Björkqvist, Kaj (European Journal of Social Science Education and Research, 2020)
The objective of the study was to investigate coping strategies and the experience of mental health interventions in Rwandans traumatised by their experiences during the 1994 genocide and its aftermath, living in Belgium and Finland. A questionnaire was completed by 341 Rwandans above 20 years of age (166 males, 175 females), with the purpose to investigate similarities and differences in coping strategies and psychological interventions in the two host countries. The participants were also interviewed. The results show that Rwandans in Belgium were more satisfied than those living in Finland with the therapeutic interventions, survivors’ group activities, and social support they had received in their host country. Rwandans in Finland, on the other hand, relied more on psychopharmaca and the use of alcohol as coping mechanisms than those living in Belgium.